No one writes to the colonel, and other stories [compact disc, unabridged] - García Márquez, Gabriel, 1927-2014 (Blackstone Audio, Inc., 2013)
Nobel Prize winning author Gabriel Garcia Marquez is known as a masterful storyteller. The stories in this mesmerizing short story collection, written with compassionate realism and wit, depict the disparities of town and village life in South America, of the frightfully poor and outrageously rich, of memories and illusions, and of lost opportunities and present joys.